(untitled) (Maʿālim al-Qurʾān wa al-Sunnah, 2018)
The applications of information and communications technologies (ICT) have become an important instrument of education nowadays. Besides being as tools for presentation and communication, there are many more ICT tools that could help the teaching and learning process. In the field of hadith (Prophetic tradition), there are many ICT applications that have been developed. The applications were developed mainly to ease the Muslim to get close and comprehend their second primary source of religion legislation which is their Prophet's hadith. The functions of the applications were rapidly upgraded besides its ability to digitizing the resources, it can store huge amount of data, facilitate quick access to databases, analyze and classify the data simultaneously. Thus, this study tries to look over the integration of the applications in the study of hadith in Malaysian public universities whether it being exposed, integrated or consolidated. Moreover, this study also tries to ponder over the lecturers’ perception, acknowledgment, skill level as well as the barriers hindered the integration of the applications. The findings of this study are most Malaysian public universities lecturer are skillful at using applications related hadith, most of them accepted the new technology well and integrated it into their teaching and there is no barrier of integrating ICT at their institution. Instead, their institutions offered full support for the integration. However, there is some disagreement from some lecturer for the full integration of ICT in the study of hadith for their opinion that the study of hadith must persevere its traditional method of teaching.